The Role of Labor Unions on Employee Performance at Mason Elephant Park and Lodge - Suarjaya, I Nyoman; Wisnawa, I Made Bayu (Jurnal Manajemen Pelayanan Hotel, 2024)
The decline in the Sumatran elephant population due to deforestation and hunting has led to the establishment of PT. Wisatareksa Gajah Perdana, known as Mason Elephant Park and Lodge in 1997, which serves as a sanctuary for this endangered species. With 291 employees, PT. Wisatareksa Gajah Perdana, the company owning this wildlife park, has the potential to form a labor union. FSP PAR KSPSI PT. Wisatareksa Gajah Perdana is a labor union established to fight for employee rights, including compensation, leave, work environment, and other issues that cannot be resolved individually. However, several problems have arisen involving the company and its employees, such as the company prioritizing profit over employee rights, a lack of understanding of labor union regulations and laws. Therefore, research is needed to determine the role of the labor union in the performance of employees at PT. Wisatareksa Gajah Perdana. This article aims to explore the impact of the labor union on employee performance at Mason Elephant Park and Lodge, as well as the challenges faced by the company and its employees. Keywords:Labor Union, Employee performance,Employee right, Tourism, Human resources